IMPLEMENTATION OF MULTICULTURAL EDUCATION TO ‎STRENGTHEN SOCIAL STUDIES LEARNING - Irsan; Riyan Maulana (CV Naskah Aceh, 2024)
This research aims to explore the implementation of multicultural education in the education system in Indonesia, as well as its impact on character formation and tolerance among students. In this research, a qualitative approach was used with a case study method in several schools that implemented a multicultural education curriculum. Data was collected through in-depth interviews with teachers, students, as well as analysis of curriculum documents and school activities. The research results show that multicultural education plays an important role in increasing students' understanding of cultural, racial and religious diversity, as well as strengthening attitudes of tolerance and mutual respect between each other. However, challenges in its implementation include a lack of in-depth understanding of the concept of multiculturalism among educators, as well as limited facilities that support optimal implementation of the program. This research suggests the need for more intensive training for teachers and the development of supporting resources in order to create a more inclusive and harmonious educational environment.